The management system of marine fisheries and other coastal resources in Palawan, Philippines concepts, experiences and lessons. - Pido, M.D., Pomeroy, R.S., Katon, B.M., Carlos, M.B. and Sandalo, A.C., eds. (Makati, Philippines ICLARM, 1996)
Fisheries Co-Management Research Project Research Report No.4
Keywords: Coastal resources